2022
DOI: 10.1111/psyp.14032
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of aerobic exercise on conflict suppression, response inhibition, and processing efficiency underlying inhibitory control processes: An ERP and SFT study

Abstract: Aerobic exercise has been identified as an effective strategy for transiently enhancing inhibitory control, an ability to suppress irrelevant distractors while focusing on relevant information in facilitating the implementation of goal‐directed behavior. The purpose of this study was to employ a go/no‐go version of the redundant‐target task and event‐related potential to further determine whether inhibitory control at the perceptual and response levels as well as their underlying processing capacity and neuroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…As for the influence of physical exercise on inhibition, many studies believe that physical exercise can improve the inhibition of individuals. Kao’s research has shown that just 20 min of aerobic exercise can improve the inhibition control of individuals [ 26 ]. Nouchi used the Stroop task to measure inhibition in middle-aged and older women.…”
Section: Discussionmentioning
confidence: 99%
“…As for the influence of physical exercise on inhibition, many studies believe that physical exercise can improve the inhibition of individuals. Kao’s research has shown that just 20 min of aerobic exercise can improve the inhibition control of individuals [ 26 ]. Nouchi used the Stroop task to measure inhibition in middle-aged and older women.…”
Section: Discussionmentioning
confidence: 99%
“…In the step 2, changes in IC and aerobic capacity were not significantly predictive of changes in language, mathematics, and overall academic performance (Fs [2,69] < 2.81, ps > 0.07, R 2 s < 0.27, ∆R 2 s < 06). In the step 3, a significant model was found for language, mathematics, and overall academic performance (Fs [1,68] > 7.99, ps < 0.04, R 2 s > 0.27, ∆R 2 s > 0.21), with the interaction between changes in IC and aerobic capacity predicting language, mathematics, and overall academic performance (see Table 4).…”
Section: Test Of the Moderation Model Of Inhibitionmentioning
confidence: 99%
“…
Overweight children are at risk for the poorer physical health and cognitive abilities, especially inhibitory control, which reflects the ability to resist distractors and override prepotent responses. [1][2][3] During maturation, overweight children displayed impaired inhibitory control compared to their healthy weight peers. [4][5][6] Such an obesity-related impairment in inhibitory control can be manifested by poor performance during tasks requiring
…”
mentioning
confidence: 99%
“…A control condition of seated rest was expected to have either no effect or a negative effect on the neural responses to attended vs. unattended stimuli (i.e., relatively decreased/increased neural activations in response to attended/unattended stimuli after rest). While the majority of studies reveal no significant impact of a seated rest condition on cognitive measures, a subset of them does suggest potential detrimental effects 32 34 .…”
Section: Introductionmentioning
confidence: 99%